Kinerja Sistem Hybrid Radio Frequency Energy Harvesting Pada Sistem Komunikasi V2V - Meyra Chusna Mayarakaca; Annysa Aprilya; Faridatun Nadziroh; Anang Budikarso (Politeknik Negeri Malang, 2024)
This article investigates the impact of hybrid Radio Frequency Energy Harvesting (RF-EH) techniques on cooperative Vehicle-to-Vehicle (V2V) communications systems. The energy harvesting (EH) process is carried out in the vehicle or vehicle transmitter as a source using the Time Switching (TS) protocol and in the vehicle or relay vehicle using the Power Splitting (PS) protocol. The transmitter or source vehicle obtains the RF signal for the EH process from the base station (BS), while the relay vehicle obtains the RF signal from the transmitter or source vehicle. System performance is presented with Outage Probability (OP) values ​​for different EH parameters, namely, time switching factor, α and power splitting factor â. From the simulation results, all parameters influence the OP value. The higher the value of the RF-EH parameters (α and â) results in a lower OP value. For noise power, N_0 = -100 dBm, the best OP value for α = 0.7 is 0.1214 and the best OP value for â = 0.8 is 0.1557.